Adjunctive Aripiprazole Treatment for Risperidone-Induced Hyperprolactinemia: An 8-Week Randomized, Open-Label, Comparative Clinical Trial - Zhao, Jingyuan (PLoS One, 2015)
OBJECTIVE: The present study aimed to evaluate the efficacy and safety of adjunctive aripiprazole treatment in schizophrenia patients with risperidone-induced hyperprolactinemia. METHODS: One hundred and thirteen patients who were receiving a stable dose of risperidone were randomly assigned to either adjunctive aripiprazole treatment (10 mg/day) (aripiprazole group) or no additional treatment (control group) at a 1:1 ratio for 8 weeks. Schizophrenia symptoms were measured using the Positive and Negative Syndrome Scale (PANSS). Rating scales and safety assessments (RSESE, BARS, UKU) were performed at baseline and at weeks 4 and 8. Serum levels of prolactin were determined at baseline and at weeks 2, 4, 6 and 8. Metabolic parameters were determined at baseline and again at weeks 4 and 8. RESULTS: One hundred and thirteen patients were enrolled in this study, and 107 patients completed the study (54 in the aripiprazole group, and 53 in the control group). PANSS-total scores in the aripiprazole group decreased significantly at week 4 (P = 0.003) and week 8 (P = 0.007) compared with the control group. PANSS-negative scores in the aripiprazole group also decreased significantly at week 4 (P = 0.005) and week 8 (P< 0.001) compared with the control group. Serum levels of prolactin in the aripiprazole group decreased significantly at week 2 (P< 0.001), week 4 (P< 0.001), week 6 (P< 0.001) and week 8 (P< 0.001) compared with the control group. There were no significant differences in changes of Fasting Plasma Glucose, Total cholesterol, Triglycerides and High Density Lipoprotein within each group at week 4 and 8 execpt low density lipoproteins. There was no significant difference in the incidence of adverse reactions between the two groups. CONCLUSIONS: Adjunctive aripiprazole treatment may be beneficial in reducing serum levels of prolactin and improving negative symptoms in schizophrenia patients with risperidone-induced hyperprolactinemia. TRIAL REGISTRATION: chictr.org ChiCTR-IOR-15006278